Description Of Stress Levels In Pulmonary Tuberculosis Patients Undergoing The Intensive Phase Of Treatment In Hospital And Puskesmas - Joseph Partogi Sibarani (CV. Inara, 2024)
The purpose of this study is to characterize the amount of stress experienced by tuberculosis patients receiving intensive phase therapy in hospitals and healthcare facilities. This study has a cross sectional design and is a descriptive observational study. 100 samples of tuberculosis patients who were receiving intense phase treatment were used in this investigation. With the consecutive sampling technique, how to choose the sample. Direct interviews with the research sample were used to gather data. Utilizing univariate analysis, research data were examined. According to the study's findings, 75% of the research sample's participants were men and 25% were women. The majority 26% are between the ages of 56 and 65. Up to 42% of people are receiving treatment for 6 to 8 weeks. The majority of pulmonary tuberculosis patients (33%) were found to have moderate levels of stress. Patients with pulmonary tuberculosis who were male, aged 36 to 45, and receiving treatment for the disease for six to eight weeks were found to have the most mild levels of stress. The study's findings indicate that the most mild levels of stress are felt by tuberculosis patients who are undergoing the intensive phase of therapy.